Training small ruminant producers on the integrated herd management package through behavior change communication in central Mali - Sow, Ahmadou; Sissoko, Oumou; Dao, M.; Rekik, Mourad; Hoek, Rein van der; Amole, Tunde A.; Idoudi, Z.; Rudiger, Udo; Tebourbi, Ons; Marshall, Karen; Dione, Michel M. (International Livestock Research Institute, 2025)
Small ruminant farmers in Mali face ongoing challenges in health, nutrition, and reproduction management. To help, stakeholders delivered comprehensive training modules on integrated herd health management codeveloped by the CGIAR Sustainable Animal and Aquatic Foods program, the CGIAR Initiative on Sustainable Animal Productivity, and partners. These trainings reached 2,577 small ruminant producers across 13 communes in Segou and Sikasso, led by “livestock champions” on a full cost recovery basis.